Who bears the costs of inflation? Euro area households and the 2021-2022 shock - Filippo Pallotti; Gonzalo Paz Pardo; Jirka Slacalek; Oreste Tristani; Giovanni L. Violante (European Central Bank (ECB), 2023)
We measure the heterogeneous welfare effects of the recent inflation surge across households in the Euro Area. A simple framework illustrating the numerous channels of the transmission mechanism of surprise inflation to household welfare guides our empirical exercise. By combining micro data and aggregate time series, we conclude that: (i) country-level average welfare costs-expressed as a share of 2021-22 income- were larger than a typical recession, and heterogeneous, e.g., 3% in France and 8% in Italy; (ii) this inflation episode resembles an age-dependent tax, with the elderly losing up to 20%, and roughly half of the 25-44 year-old winning; (iii) losses were quite uniform across consumption quantiles because rigid rents served as a hedge for the poor; (iv) nominal net positions are the key driver of heterogeneity across-households; (v) the rise in energy prices generated vast variation in individual-level inflation rates, but unconventional fiscal policies were critical in shielding the most vulnerable households.
Keywords: D12; D14; D31; E21; E52; E58; 330; Inflation; Redistribution; Household Heterogeneity; Net Nominal Positions; Labor Income; Consumption; Housing; Fiscal Support